1950
DOI: 10.1136/jech.4.3.143
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Respiratory Tuberculosis in Relation to Housing Conditions in Edinburgh: I.--The Pre-War Period

Abstract: * The standard by which overcrowding is defined is that of the 1935 Housing (Scotland) Act, details of which are given on p. 155.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…The transmission of TB to children in a nuclear family (composed of father, mother, and children) with adult pulmonary TB was uncertain. [25][26][27] Children who share a house with an adult pulmonary TB sufferer will directly suffer from TB in a shorter period (< 6 months). Generally, the immune system of chil-4 28 Staying longer with an adult pulmonary TB sufferer did not significantly ascertain whether the children suffered from TB.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of TB to children in a nuclear family (composed of father, mother, and children) with adult pulmonary TB was uncertain. [25][26][27] Children who share a house with an adult pulmonary TB sufferer will directly suffer from TB in a shorter period (< 6 months). Generally, the immune system of chil-4 28 Staying longer with an adult pulmonary TB sufferer did not significantly ascertain whether the children suffered from TB.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,6 Poor housing conditions, including residential crowding and household disrepair, have been shown to elevate the risk of household accidents, asthma, tuberculosis, other respiratory infections, and all-cause mortality. 1,[7][8][9] Conversely, improvements in housing may favor cardiovascular and respiratory health. 10 Few studies have examined the link between housing quality and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Homelessness is demonstrably bad for people's health, but so is living in dilapidated, overcrowded, damp or cold housing (Lowry 1990). During the 1950s, a number of British human ecological studies established a statistical association between poor housing conditions and premature mortality (Stein 1950, Hare 1956. A recent survey that used double-blind procedures to measure dampness and health in 597 houses in the UK showed that adults living in damp and mouldy dwellings were more likely to report a wide range of symptoms (nausea, vomiting, constipation, blocked noses, breathlessness, backache, aching joints, fainting and 'bad nerves') than those living in dry dwellings.…”
Section: Poor Quality Housingmentioning
confidence: 99%